Does online voting change the outcome? Evidence from a multi-mode public policy referendum. (June 2017) - Mellon, Jonathan; Peixoto, Tiago; Sjoberg, Fredrik M
Abstract: Do online and offline voters differ in terms of policy preferences? The growth of Internet voting in recent years has opened up new channels of participation. Whether or not political outcomes change as a consequence of new modes of voting is an open question. Here we analyze all the votes cast both offline (n = 5.7 million) and online (n = 1.3 million) and compare the actual vote choices in a public policy referendum, the world's largest participatory budgeting process, in Rio Grande do Sul in June 2014. In addition to examining aggregate outcomes, we also conducted two surveys to better understand the demographic profiles of who chooses to vote online and offline. We find that policy preferences of online and offline voters are no different, even though our data suggest important demographic differences between offline and online voters. Highlights: The 2014 Participatory budgeting vote in Brazil saw large demographic differences between online and offline voters. Only 31% of online voters say they would have voted if there had not been an online option. Despite demographic differences, there is no systematic difference in vote choices between online and offline electorates.